Answers

The Brainliest Answer!
2014-10-17T20:20:19+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
x+y=0 \\  x=-y

 (\frac{x}{y} )2014 =  (\frac{-y}{y} )2014=(-1)*2014 = -2014
2 5 2
thank you very much
i sent an question please solve it
thanks..
can u solve it
2014-10-17T20:25:56+05:30
X+y=0 => x=-y then (x/y)2014=(-y/y)2014=-1*2014=-2014

1 1 1
thank u i sent one more question please solve it